INFLUENCE OF POSITIVE MOTIVATION TO EDUCATING, AS A MECHANISM OF PROFESSIONAL PREPARATION OF FUTURE SPECIALISTS - Гейченко, С. П.; Свірська, Т. Ф.; Скидан, І. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
This article discusses pedagogical conditions ensuring the successful mastery of knowledge and skills formation. Proved that the interest in physical education as an academic and extracurricular forms of employment can be increased, if the means to use those kinds of physical activity, which are more popular with this group of students